Currency swaps - Coyle, Brian (Chicago, Ill. : Glenlake Pub. Co. ; New York : AMACOM, 2000)
"The text describes the evolution of this financial instrument and the present day importance it has in debt and interest rate risk management. It examines the features of currency swaps and the process by which the counterparties reach agreement. Through practical examples it illustrates the role of banks and explains swaps pricing and the value of a swap."--BOOK JACKET.
1. Introduction -- 2. Features of Currency Swaps -- 3. The Role of Banks -- 4. Types of Currency Swap -- 5. Asset Swaps -- 6. Swaps Pricing and the Value of a Swap -- 7. Why Use Swaps? -- 8. Arranging a Swap.
Includes index.
Keywords: Currency swaps